Longitudinal Changes in Muscle Mass and Function in Older Men at Increased Risk for Sarcopenia - The FrOST-Study - Kemmler, Wolfgang; von Stengel, Simon; Schöne, Daniel (Journal of Frailty & Aging, 2019)
BACKGROUND: Declines in muscle mass and function are inevitable developments of the advanced aging process. Corresponding dimensions of longitudinal changes in at-risk populations are still scarce although clinically relevant. The present study monitored changes in morphologic and functional sarcopenia criteria related to sarcopenia in older men with low muscle mass over a period of 24 months. OBJECTIVES: The main objective of the present study was to determine whether changes in muscle mass and function were comparable across the body. Our hypothesis was that both (1) fat free mass (FFM) and (2) function decline at a significantly higher rate in the lower versus the upper extremities. DESIGN: We conducted an observational study of 24 months. SETTING: Community dwelling men living in the area of Northern Bavaria were initially included in the Franconian Sarcopenic Obesity (FranSO) study by the Institute of Medical Physics University of Erlangen-Nürnberg, Germany. PARTICIPANTS: One hundred and seventy-seven (177) men (77.5±4.5 years) within the lowest skeletal muscle mass index (SMI) quartile of the FranSO study were included in the present 24 month analysis. MEASUREMENTS: Fat free mass (direct-segmental, multi-frequency Bio-Impedance-Analysis (DSM-BIA)), handgrip strength (hand-dynamometer) and 10-m habitual gait velocity (photo sensors) were assessed at baseline and 24-month follow-up. RESULTS: Lower extremity fat free mass (LEFFM: -2.0±2.4%), handgrip strength (-12.8±11.0%) and gait velocity (-3.5±9.0%) declined significantly (p<.001) during the follow-up period, while upper extremity FFM was maintained unchanged (UEFFM: 0.1±3.1%). Changes in LEFFM were significantly higher (p<.001) compared with UEFFM, however contrary to our expectation the decline in handgrip strength representing upper extremity muscle function was 3.7-fold higher (p<.001) than the decline in gait velocity. CONCLUSION: Medical experts involved in diagnosis, monitoring and management of sarcopenia should consider that parameters constituting morphologic and functional sarcopenia criteria feature different rates of decline during the aging process.
CRIS-Team Scopus Importer:2019-05-14
Keywords: dynamopenia; gait velocity; handgrip strength; Late-Life Function and Disability Instrument; Skeletal muscle mass